A conceptual framework for the Impact of financial crime towards the financial performance of Islamic financial institutions - Redzuan, Nur Harena; Abdul Rahman, Nur Hasnida; Abdullah, Adam (IIUM Press, International Islamic University Malaysia International Islamic University Malaysia (IIUM), 2019)
This paper aims to assess the reputation of risk faced by Islamic financial institutions due to financial crime activities. There is an increasing trend in financial crime activities at banking institutions. For Islamic financial institutions that are founded based on Sharīʽah, the usage of Islamic financial instruments for criminal activities undermines the integrity of the Islamic financial system itself. It would also tarnish Islamic financial institutions’ reputation that supposed to operate with Islamic principles against any criminal activities. Trust or the public confidence towards the integrity of Islamic financial institutions would also be distracted as being associated with financial crime activities signaling that the Islamic financial institutions' profit is eroded by criminal activities. This has raised concerns and questions about the reputation of Islamic financial institutions. A proposed conceptual framework discusses how trust and reputation risk affect the Islamic financial institutions’ performance when the financial crimes happen.